The Approach to Fiqh Tafsir in the Tafsir of Al-Ahkam - Muti Atul Hasanah; Dzulkifli Hadi Imawan (KOLABORASI: Journal of Multidisciplinary, 2024)
This study examines the fiqh tafsir approach in Tafsir al-Ahkam by Abdul Halim Hasan Binjai, a prominent Indonesian scholar known for his moderate and inclusive legal thought. Using a qualitative library research design, the study analyzes primary and secondary sources related to Abdul Halim Hasan’s biography, intellectual background, interpretive orientation, and examples of legal interpretation in his work. The findings show that Tafsir al-Ahkam was written to help Muslims understand legal verses of the Qur’an while bridging differences of opinion among schools of thought. Abdul Halim Hasan consistently presents various juristic views without excessive sectarianism, reflecting a balanced, contextual, and academically open approach to Islamic law. His interpretation emphasizes the importance of justice, trust, and legal reasoning grounded in the Qur’an, Hadith, and ijtihad. Therefore, Tafsir al-Ahkam represents a significant contribution to the development of fiqh-oriented Qur’anic interpretation in Indonesia. It highlights his contribution to moderation in Indonesian Islamic scholarship.